Parental Socioeconomic Status, Locus of Control, Social Media, and Peer Pressure as Determining Factors of Risky Sexual Behavior in College Students - Bamidele Joke Fowowe-ogunmilugba (Indonesian Gender and Society Journal, 2023)
This research focuses on identifying factors that influence risky sexual behavior among college students. Risky sexual behavior refers to sexual activities that can increase the risk of transmitting sexually transmitted diseases and unwanted pregnancy. In this context, several factors have been identified as major determinants, including parental socioeconomic status, locus of control, social media use, and peer pressure. The aim of this research is to analyze and understand the influence of several factors on risky sexual behavior among students. This research uses a descriptive survey research design with qualitative research methods. Two hundred forty (240) male and female undergraduate students served as study participants. Data collection was carried out using reliable instruments: The main results of the study are conclusive Primary emphasis should be placed on providing sufficiently informative sex education services to students at universities to equip them with valid facts about safe sexual practices. The implications of this research have a broad impact in both academic and practical contexts, the findings of this research can enrich the academic literature regarding risky sexual behavior, in particular by highlighting the role of factors such as parental socioeconomic status, locus of control, social media use, and pressure. friends of the same age.